The real effect of partial privatization on corporate innovation: Evidence from China's split share structure reform - Tan, Yongxian; Tian, Xuan; Zhang, Xinde; Zhao, Hailong (Journal of Corporate Finance, 2020)
We examine the real effect of partial privatization on corporate innovation. To establish causality, we explore plausibly exogenous variation in the expectation of further partial privatization generated by China's split share structure reform, which mandatorily converts non-tradable shares into freely tradable shares and opens up the gate to the further privatization of state-owned enterprises. We find that partial privatization prospects have a positive effect on corporate innovation. A better alignment of the interests of government agents with those of private shareholders and improved stock price informativeness appear to be two plausible underlying mechanisms. Our paper sheds new light on the real effects of partial privatization.